PROVOCĂRILE GENERAȚIEI MILLENNIALS PENTRU BIBLIOTECA MUNICIPALĂ „B.P. HASDEU” - HARJEVSCHI, director general, BM „B.P. Hasdeu”, Mariana (BIBLIOPOLIS, 2020)
The article describes the new libraries’ challenges considering users. As public institutions libraries continue to be as anchors in the community, the library users are major drivers to innovations. Author describes how the Millennial Generation, as consumes and as potential library staff members interact and engage with information resources and personnel in a multiplicity of ways, at any time, in any location a specific approach should be developed on institutional level.